2016
DOI: 10.1177/1742395315625099
|View full text |Cite
|
Sign up to set email alerts
|

The use of dialogue tools to promote dialogue-based and person-centred patient education for people with type 2 diabetes

Abstract: The application of dialogue tools to engender participatory patient education is highly dependent on educators' and participants' understanding and use of dialogue tools in practice. This implies that substantial educator skills are needed to facilitate dialogue and participation in patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Training HCPs to act as facilitators to promote a collaborative relationship and include participants’ experienced needs, preferences and values in diabetes self‐management education and support, linking health topics to the context of the particular participants, may also be effective components. This is consistent with other studies that describe the potential for promoting person‐centredness as dependent on HCP’s communication and facilitation skills . A review by Fisher et al identified two crucial steps HCPs must complete before tools to enhance and encourage improvements in self‐management can be used.…”
Section: Discussionsupporting
confidence: 84%
“…Training HCPs to act as facilitators to promote a collaborative relationship and include participants’ experienced needs, preferences and values in diabetes self‐management education and support, linking health topics to the context of the particular participants, may also be effective components. This is consistent with other studies that describe the potential for promoting person‐centredness as dependent on HCP’s communication and facilitation skills . A review by Fisher et al identified two crucial steps HCPs must complete before tools to enhance and encourage improvements in self‐management can be used.…”
Section: Discussionsupporting
confidence: 84%
“…From a practical perspective, the educational approaches used by renal dietitians must be effective, as well as pragmatic because of the resource and time constraints experienced by renal dietitians . Alternative educational approaches could include the use of question prompt lists; reducing the cognitive burden; using dialogue boards; or conversation maps and increasing the actionability of renal diet patient education resources . Further studies on the usefulness of improved printed patient education materials (such as diet sheets) and supermarket tours should also be undertaken …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the facilitators used probes in the form of images, statements and quotations regarding physical activity developed at the Steno Diabetes Center to foster active participation and interaction among participants . Using probes in focus group interviews has been shown to encourage participants to reflect, engage in dialogue, and verbalize experiences .…”
Section: Methodsmentioning
confidence: 99%